Abnormal ECA-Binding Membrane Glycans and Galactosylated CAT and P4HB in Lesion Tissues as Potential Biomarkers for Hepatocellular Carcinoma Diagnosis - Kong, Ying; Chen, Hao; Chen, Mengyu; Li, Yongshuai; Li, Jiarong; Liu, Qi; Xiong, Huan; Guo, Tangxi; Xie, Yan; Yuan, Yufeng; Zhang, Xiao-Lian (Frontiers in Oncology, 2022)
Hepatocellular carcinoma (HCC) is one of the most common types of cancer. Despite decades of research efforts, search for novel biomarkers is still urgently needed for the diagnosis of HCC and improvement of clinical outcomes. Previous studies of HCC clinical biomarkers have usually focused on serum and urine samples (e.g. serum Alpha-fetoprotein (AFP). However, cellular membrane proteins in lesion tissues are less used in HCC diagnosis. Abnormal expression of membrane glycoproteins in tumor lesions are considered as potential targets for tumor diagnosis and tumor therapies. Here, lectin array has been employed to screen and identify abnormal glycopatterns and cellular membrane glycans in HCC lesion tissues compared with adjacent non-tumor tissues. We found that significantly less expression of Erythrina cristagalli (ECA) lectin binding (Galβ1-3/β1-4) glycans on the cellular membrane of HCC lesion tissues compared with those of adjacent non-tumor tissues. Immunohistochemistry analysis further showed ECA-binding ability on the membrane proteins of HCC tissues progressively decreased in different tumor-node-metastasis (TNM) stages (stage I to stage III) as the malignancy of liver cancer increased. Receiver operating curve (ROC) analysis showed ECA-binding ability yielding a sensitivity of 85% and specificity of 75%, and a combination of ECA and AFP has better clinical diagnostic efficiency, yielding a sensitivity of 90% and specificity of 85%, than ECA or AFP assay alone. ECA pull-down followed by mass spectrometry further showed that significantly less expression of ECA binding membrane catalase (CAT) and prolyl 4-hydroxylase beta polypeptide (P4HB) in HCC tissues compared with the adjacent non-tumor tissues. And the abnormal increased expression of total CAT and P4HB and decreased expression of galatosylated membrane CAT and P4HB in HCC cell lines were correlated with HCC metastasis status. Our findings suggest that abnormal declined ECA-binding galatosylated membrane glycans and two galatosylated-CAT and P4HB glycoproteins in lesion tissues as potential biomarkers in diagnosis and/or metastasis prediction for HCC.